The performance of robust correlation coefficient under contaminated bivariate data - Zakaria, Nur Amira; Abdullah, Suhaida; Ahad, Nor Aishah; Yusof, Norhayati; Syed Yahaya, Sharipah Soaad (2016)
Classical correlation coefficient is a powerful statistical analysis when measuring a relationship between the bivariate normal distribution when the assumptions are fulfill.However, this classical correlation coefficient performs poor in the presence of outlier. Thus, this study aims to propose new version of robust correlation coefficient based on MAD n and S n .The performance of this proposed robust correlation coefficient will be evaluated based on three indicators which were the value of the correlation coefficient, average bias and standard error. The proposed procedure is expected to produce MAD n correlation coefficient and S n correlation coefficient.Both coefficients are expected to perform better than classical correlation coefficient and resistance to the outlier.